(untitled) (Revista científica Olimpia, 2020)
The purpose of this article is to make theoretical reflections on the importance of planning psychological preparation in volleyball athletes at school ages as a pedagogical and psychological process of developing the psychic qualities and properties of the athlete, necessary for the efficient realization of the sports activity in order to guarantee a state of psychological predisposition in the extreme conditions of training and competitions.